Ответ: ![a=7;b=-3 a=7;b=-3](https://tex.z-dn.net/?f=a%3D7%3Bb%3D-3)
Пошаговое объяснение:
\left \{ {{a=7} \atop {2(7)-b=17}} \right. =>\left \{ {{a=7} \atop {-b-3=0}} \right. => \left \{ {{a=7} \atop {b=-3}} \right." alt="\left \{ {{a=7} \atop {2a-b=17}} \right. => \left \{ {{a=7} \atop {2(7)-b=17}} \right. =>\left \{ {{a=7} \atop {-b-3=0}} \right. => \left \{ {{a=7} \atop {b=-3}} \right." align="absmiddle" class="latex-formula">
![a=7;\\b=-3 a=7;\\b=-3](https://tex.z-dn.net/?f=a%3D7%3B%5C%5Cb%3D-3)